Stunting Prevention Education and Training by Making Toddler Food Companion Snacks in Masjid Village, Samarinda City - Wildan Dzakiy; Putri Agustiningrum; Purwo Setiyo Nugroho (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2022)
Stunting can occur because one of the factors is the mother's education which has an impact on the mother's low knowledge about stunting and also inappropriate maternal parenting. The results of observations at the intervention site show that there are still people who ignore the importance of nutritional intake and most of the people have less knowledge and awareness about stunting prevention. In addition, children under five in the area also do not like vegetables. Therefore, this community service activity is carried out with the aim of increasing the understanding and skills of mothers in preventing stunting in toddlers and processing vegetables that can be interesting for consumption by toddlers. The target of this activity is mothers who have toddlers in the Masjid Village, Samarinda City. The activity was carried out on December 9, 2021 through education and training. The media used are leaflets. This activity is evaluated by making direct observations during the implementation of the activity. The result of this activity is that the community begins to understand stunting prevention efforts and is skilled in processing vegetables into more attractive spring roll snacks for consumption by toddlers as an alternative to healthy snacks to prevent stunting.